Is Alteration of Tuning Property in Cervical Vestibular-Evoked Myogenic Potential Specific for Ménière’s Disease? - Murofushi, Toshihisa; Tsubota, Masahito; Suizu, Ryota; Yoshimura, Eriko (Frontiers in Neurology, 2017)
Objective: To show sensitivity and specificity of cVEMP (cervical vestibular evoked myogenic potential) tuning property test to Ménière’s disease (MD) in comparison with healthy controls and patients with other vestibular diseases. Subjects: Totally 92 subjects (50 women and 42 men, 20-77 years of age) were enrolled in this study. Subjects were composed of 38 definite unilateral MD patients, 11 unilateral benign paroxysmal positional vertigo (BPPV) patients, 14 vestibular migraine (VM) patients, 19 unilateral vestibular neuritis (VN) patients, and 10 healthy controls. Methods: The subjects underwent cVEMP testing to 500 Hz and 1000 Hz short tone bursts (STB) (125 dBSPL). The corrected amplitudes of the first biphasic responses (p13-n23) (cVEMP) were measured. Then, a tuning property index (the 500-1000 Hz cVEMP slope) was calculated. Results: The area of under the ROC curve (AUC) was 0.75 in comparison with other vestibular disease patients, while AUC was 0.77 in comparison with other vestibular disease patients plus healthy controls. The best cut-off point of the 500-1000 Hz cVEMP slope was -19.9. Sensitivity of the tuning property test to MD was 0.74, while specificity was 0.76 to other vestibular disease patients. Conclusion: The tuning property test of cVEMP is useful as a screening test of MD.